Metal recovery from spent lithium-ion batteries cathode materials: Comparative study of sugar-based reductants - Emenike G. Okonkwo; Greg Wheatley; Yang Liu; Yinghe He (Journal of Hazardous Materials Letters)
Sugars and sugar-rich agricultural by-products are cheaper and eco-friendly alternatives to conventional reductants used in recovering metals from spent lithium-ion batteries. Still, they are rarely used due to a poor understanding of their performance and reaction chemistry. In this study, two hypotheses bearing on the role of chemistry and influence of non-sugary organic compounds (impurities) on the performance of sugars, namely: glucose, fructose and sucrose, and a parent sugar-rich agro-industrial by-product – molasses, as reductants in the leaching of Li, Co, Mn and Ni from spent lithium-ion battery cathode material were tested. Statistical analysis using ANOVA revealed that the performance of the sugars and molasses are similar with >85% Mn, >88% Ni, >88%Co and >98% Li leached at 90 °C and 60 min. This shows that the presence of non-sugar organic compounds does not hamper the performance of the sugars-based reductants. The performance of the sugars relies more on temperature than chemistry. Furthermore, evaluation of the oxidation pathway hints at a potential inhibition of secondary oxidation reactions at lower temperatures. This study provides statistically validated proof that the performance of sugarcane molasses, even at lower concentration, is equipollent to the pure sugars in the leaching of critical metals from spent lithium-ion batteries.